Revisiting the phosphorite deposit of Fontanarejo (central Spain): new window into the early Cambrian evolution of sponges and the microbial origin of phosphorites. (29th July 2022) - Reitner, Joachim; Luo, Cui; Suarez-Gonzalez, Pablo; Duda, Jan-Peter
Abstract: Fossils within early Cambrian phosphorites worldwide are often well preserved due to early diagenetic permineralization. Here, we examine the fossil record contained within phosphorites of the Lower Cambrian Pusa Formation (late Fortunian to Cambrian Stage 2) in Fontanarejo, central Spain. The sedimentology and age of these phosphorites have been controversial and are here reviewed and discussed, providing also an updated geological map. The Pusa Formation is composed of fine clastic sediments that are partly turbiditic, with channels of quartz-rich conglomerates and abundant phosphorites in the upper part of the succession. The microfacies and mineralogy of these channel deposits are studied here for the first time in detail, showing that they are mainly composed of subspherical apatite clasts, with minor mudstone intraclasts, quartzite and mica grains. Numerous sponge spicules, as well as entirely preserved hexactinellid sponges and demosponges, were collected within these phosphorites and likely represent stem groups. In addition to sponges, other fossils, such as small shelly fossils (SSF) of the mollusc Anabarella sp., were found. The phosphorites exhibit multiple evidence of intense microbial activity, including diverse fabrics (phosphatic oncoidal-like microbialites, thrombolites, stromatolites and cements) and abundant fossils of filamentous microbes that strongly resemble extant sulphur-oxidizing bacteria. Our findings strongly suggest that microbial processes mediated the rapid formation of most of the Fontanarejo apatite, probably accounting for the exceptional preservation of fragile fossils such as sponge skeletons. The apparent presence of taxonomically diverse hexactinellid and demosponge communities at the lowermost Cambrian further corroborates a Precambrian origin of the phylum Porifera.